Mohsin Hamid's War on Error: The Reluctant Fundamentalist as a Post-Truth Novel. Issue 2 (August 2018) - Bahrawi, Nazry
Abstract : In contemporary political discourse, the term 'post-truth' denotes rhetorical techniques often directed at garnering popular support. Post-truth techniques were, for instance, said to have characterised Donald Trump's presidential campaign in the United States as well as the Brexit lobby in the United Kingdom. This article proposes an alternative interpretation of 'post-truth', approaching it as a challenge to dominant systems of knowledge expressed through literary narratives. This essay puts forward a consideration of 'decolonial post-truth' as a rhetorical technique inspired by Walter Mignolo's concept of decoloniality. In so doing, it engages with the countertextual through the ways in which literariness travels from the novel into everyday politics. Seeking to demonstrate the workings of decolonial post-truth through a close reading of Mohsin Hamid's The Reluctant Fundamentalist (2007), the essay positions the novel as a counter-historical text that challenges the truisms that breathe life into 9/11 Islamophobia.